Epistemological beliefs and teaching practice: a systematic literature review 2011 to 2021 - Mirko Aguilar-Valdés; Alejandro Almonacid-Fierro; Karla Valdebenito; Sergio Sepúlveda-Vallejos (International Journal of Evaluation and Research in Education (IJERE), 2024)
Teachers’ actions are grounded on their theoretical and disciplinary knowledge; however, their belief system, and in particular their epistemological beliefs, may be influencing their teaching practices. This study analyzes the scientific production between 2011 and 2021 regarding teachers’ epistemological beliefs and their relationship with teaching practice. The methodological design consists of a systematic literature review, following the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines in the Web of Science, Scopus, and ERIC databases. The sample considers 18 articles reviewed by thematic content analysis. The results report that this type of belief has a close relationship with teaching approaches, that there are certain inconsistencies with teaching practice, and that links have been established with other areas of study that enrich reflection. It seems prudent and necessary to observe this relationship from a broad, situated, and complex perspective, avoiding generalizing and polarizing the character of these beliefs, by noting that there are various factors involved between what teachers believe about knowledge and what they do in the classroom.